Comprensión lectora en alumnos de primero de secundaria de una institución educativa del Callao según su procedencia escolar - Ordiales Abad, Genoveva Sonia (2012)
This descriptive – comparative study aims to compare the levels of reading comprehension of the first year high school students of a public school of region Callao to another group formed by students of public and school private school. The study was done with a sample of 240 students (106 from the same institution, and 134 from others institutions) from both genders whose ages were 11 and 12 years old. The test Comprensión Lectora ACL 6 proposed by Catalá (2001) and adapted for our city by Ortega and Ramirez (2009), was applied to the students of the sample showing validity and reliability. The study proved that there were significant differences between the two groups related to reading comprehension; however, there were no differences in making inferences, showing a higher performance the group the students from other educational institutions.